The Method of Simultaneous Equable Approximation by Splines of Trigonometric Functions and Their Derivatives - Литвин, Олег Миколайович; Литвин, Олег Олегович; Ткаченко, Олександр Володимирович (Кам'янець-Подільський національний університет імені Івана Огієнка, 2019)
Method is presented on the best approximation by splines of trigonometric functions and their derivatives, with respect to isogeometric properties